A Rare Case of C2 Sensory Blockade with Preserved Phrenic Nerve Function in an Obstetric Patient. (31st July 2016) - Coffman, John C.; Fiorini, Kasey; Cook, Meghan; Small, Robert H.
Abstract : High neuraxial blockade is a serious complication in obstetric patients and requires prompt recognition and management in order to optimize patient outcomes. In cases of high neuroblockade, patients may present with significant hypotension, dyspnea, agitation, difficulty speaking or inability to speak, or even loss of consciousness. We report the unusual presentation of an obstetric patient that remained hemodynamically stable and had the preserved ability to initiate breaths despite sensory blockade up to C2. The presence of differential motor and sensory block documented in this case helped enable the patient to be managed with noninvasive ventilatory support until the high blockade regressed and we are not aware of any other similar reports in literature.